#### Answer

$(g-f)(x)= x^2+2x-8$

#### Work Step by Step

RECALL:
$(g-f)(x) = g(x) - f(x)$
Using the formula above gives:
$(g-f)(x) = (x^2-5)-(-2x+3)
\\(g-f)(x)= x^2-5-(-2x)-3
\\(g-f)(x)= x^2-5+2x-3
\\(g-f)(x)= x^2+2x-8$

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$(g-f)(x)= x^2+2x-8$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.